2014
DOI: 10.1118/1.4888361
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐31: Alternative VMAT Technique Reduces Total Monitor Units for Lung SBRT

Abstract: Purpose: To investigate an alternative approach to VMAT optimization for hypofractionation lung treatment which increases average aperture opening and results in lower total Monitor Units (MU) without significantly sacrificing plan quality. Methods: Benchmark Volumetric Modulated Arc Therapy (bVMAT) plans were generated for 10 lung Stereotactic Body radiotherapy (SBRT) cases using Eclipse Version 11.0.42 (Varian Medical Systems) without a maximum MU constraint. Prescriptions ranged from 40 to 54Gy in 3 to 5 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…From our results, it can be seen that there is no major difference in the plan quality with and without the MU objective function in the optimisation which agrees with the work of Clemente et al (2013), Happersett et al (2014) and Huang et al (2015). This has been verified both in terms of treatment plan and measurement comparison.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…From our results, it can be seen that there is no major difference in the plan quality with and without the MU objective function in the optimisation which agrees with the work of Clemente et al (2013), Happersett et al (2014) and Huang et al (2015). This has been verified both in terms of treatment plan and measurement comparison.…”
Section: Discussionsupporting
confidence: 81%
“…It is The total number of MUs were reduced by 23% by using the MU objective function. This is significantly higher than what has been reported in the study by Happersett et al (2014) study (11%). Similarly, average MU/Gy reduced from 269.0 to 204.9 which is significantly better than Huang et al (2015) (228 MU Gy −1 ) have reported.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation